A PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN PADA YAMAHA SURYANATA MOTOR AMUNTAI - Hasanah, Nurul (PPPM STIA Amuntai, 2019)
This research aims to know: (1) Yamaha Suryanata Motor promotion strategy year 2016-2017, (2) Cost promotion Yamaha Suryanata Motor year 2016-2017, (3) Sales volume Yamaha Suryanata Motor year 2016-2017, (4) promotion to sales volume at Yamaha Suryanata Motor 2016-2017. This research uses qualitative and quantitative methods, this research is conducted on Yamaha Suryanata Motor, and data taken for three years starting from 2016-2017 and calculation using monthly data consisting of promotion cost and sales volume. Data collection was done by interview method, observation, and documentation. The data analysis used is quantitative method and simple linear regression. The result of the research shows that: (1) The promotion strategy of Yamaha Suryanata Motor is done by advertising, sales promotion, and publicity, (2) Yamaha Suryanata Motor promotion expense year 2016-2017 increase, 2016 Rp 26.400.000, and year 2017 Rp 41,800,000, (3) Sales volume of Yamaha Suryanata Motor in 2016-2017 has increased, in 2016 amounted to 2680 units and in 2017 of 4225 units, (4) Test results resulted in significant effect of promotion cost on sales volume at Yamaha Suryanata Motor, with thitung = 15.29 is greater than ttable = 1.714